Biomass and methane yield of giant reed (Arundo donax L.) as affected by single and double annual harvest. Issue 3 (4th January 2021) - Ceotto, Enrico; Vasmara, Ciro; Marchetti, Rosa; Cianchetta, Stefano; Galletti, Stefania
Abstract: The replacement of silage maize with giant reed as energy crop has been proposed as a mean for reducing the need of irrigation water as well as monetary and environmental costs of cultivation. Little is known about giant reed response to within‐season harvesting, and its effect on the methane production in anaerobic digestion. The effect of three harvest schedules on yield, biomass composition and methane production of giant reed was evaluated at one site of the Po Valley, northern Italy, for three consecutive years. In a completely randomized block design with four replicates the treatments applied annually were: (i) double harvest 1: first cut at the end of June + second cut at the beginning of October (DH1); (ii) double harvest 2: first cut at the end of July + second cut at the beginning of October (DH2); (iii) single harvest at the beginning of October (SH). The crop stand was established in the year 2015 and treatments were repeatedly applied in the years 2016, 2017 and 2018. The SH treatment determined the highest average annual dry matter (DM) yield (59.0 Mg DM ha −1 ). The DM yield for treatments with double harvest was significantly lower, that is, −30% for DH1 and −15% for DH2. In terms of specific methane yield there was little advantage in harvesting biomass twice during the growing season. The average specific methane yield varied substantially between years (i.e. from 144 to 233 ml CH4  g −1  VS), and in every year the values tended to decrease with the ageing of harvested biomass. Methane yield per hectare, however, was driven by DM yield, thus SH also determined the highest average value (9110 m 3  CH4 ‐STP ha −1 ). In conclusion, the single annual harvest at the end of the growing season is an ideal strategy for maximizing methane production from giant reed. Abstract : The perennial grass giant reed has been proposed as energy crop due to its low input requirement coupled with high productivity. Little is known, however, about giant reed response to within‐season harvesting, and its effect on the methane production in anaerobic digestion. The effect of three harvest schedules on yield, biomass composition and methane production of giant reed was evaluated at one site of the Po Valley, northern Italy, for three consecutive years. We here show that a single annual harvest at the end of the growing season is an ideal strategy for maximizing methane production from giant reed.